Estimation of pollutants emissions at Ukrainian thermal power plants - Volchyn; Haponych L.S. (General Energy Institute of the National Academy of Sciences of Ukraine, 2019)
We proposed an algorithm for estimating the emission of pollutants (sulfur dioxide, dust, and nitrogen oxides) depending on the amount of supplied electric and thermal energy for each year of the operation of burning facility as a part of power unit or a boiler house. By this algorithm, we calculated the emission of sulfur dioxide at the Ukrainian thermal power plants (TPP) in 2017 and 2018. The results of calculations coincide with the available data of power plants and calculations by the standard procedure, based on using information about fuel consumption and its elemental composition. The values of SO2 concentration in dry flue gases of the Ukrainian TPP in 2017 and 2018 were 1520–5900 mg/nm3, and the gross SO2 emissions were about 620 thousand tons. The specific SO2 emissions at the Ukrainian TPP during last years take values of 14–15 g/kW h of supplied electricity as compared with the level for coal fired-power plants of EU countries of 1.2 g/kW h. This is explained by the absence of desulfurization facilities at the Ukrainian TPP and the high level of specific fuel consumption for the electricity production.By the proposed algorithm, we calculated the maximal emissions of SO2 according to the order of Ministry of Environmental Protection of Ukraine of February 16, 2018 No. 62. They were equal to 936.9 thousand tones. However, NERP envisions the decrease in SO2 emissions at the Ukrainian TPP to 51 thousand tones in 2018. Furthermore, after January 1, 2029, Ukraine must provide the satisfaction of required SO2 concentration in flue gases of Ukrainian TPP no higher that 200 mg/nm3 as follows from the Directive 2010/75/EU of the European Parliament and of the Council of 24 November 2010 on industrial emissions. The present-day level of SO2 concentration exceeds this limiting value by a factor of 8–25. To reach the European requirements, it is necessary to construct a modern gas-cleaning equipment with an efficiency no lower than 96%.